THE CATCH COMPARISON ON RAFIA ROPE AND TRADITIONAL FISH AGREGATING DEVICES IN WEST ACEH WATERS (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
West Aceh Regency has a coastline length of about 50.55 km, with an area of ​​sea waters of around 80.88 km2. This condition is inseparable from its location facing directly into the Indian Ocean which is rich in fish. Rumpon, knowned as FADs, is an artificial tool that collects fish using atractors, such as coconut leaves, areca leaves and nipah leaves and other solid objects that serve as a lure for gathering fish. Drifting FADs are non-permanent FADs and are not equipped with anchors so they drift following the movement and direction of the current, while settled FADs are FADs equipped with anchors or weights. The aim of this study was to analyze the composition of species, the amount and weight of the fish caught. The study was conducted in January-July 2018, located in West Aceh waters. The data collected is in the form of primary data, where the collection uses the experimental fishing method. Furthermore, the data were analyzed statistically using the t test. Observations of the catch were carried out for up to 18 trips to traditional and raffia rope FADs. The variables observed in this study were species composition, number and weight of fish caught in both FADs. The results showed that traditional FADs obtained as many as 7,538 fish catches (61.5%) were more than 4,821 (38.5%) raffia rope FADs, with 7 species of fish being dominated by mackerel fish. This shows that traditional FADs are more effective than raffia rope FADs.